Sheldon's practice and law of banking - Sheldon, Herbert Percival; Drover, C. B.; Bosley, R. W. B. (London : Macdonald and Evans, 1972)
The book discusses on foreign exchange including exchange control and collection of commercial papers with uniform rules.
Includes index.
Bibliography: p. [680]-681.
sju 24/01/2019
Loans
Keywords: Banking law; Negotiable instruments